Xylose yields and relationship to combined severity for dilute acid post-hydrolysis of xylooligomers from hydrothermal pretreatment of corn stover. Issue 1 (26th September 2014) - Zhang, Taiying; Kumar, Rajeev; Tsai, Yueh-Du; Elander, Richard T.; Wyman, Charles E.
Abstract : A simple and efficient process was developed for near theoretical conversion of xylooligomers (XOs), and a modified combined severity parameter (CSP) was proposed to relate severity with XOs breakdown to xylose. Abstract : To maximize yields of fermentable xylose monomer from hydrothermal pretreatment of corn stover at 200 °C, the xylooligomers-rich liquor produced was post hydrolyzed with dilute sulfuric acid over a range of times and acid concentrations. The results showed that application of 0.75% H2 SO4 at 110 °C for 180 min or 0.50% H2 SO4 at 110 °C for 240 min recovered almost 100% of the total xylose from the oligomers. Furthermore, adjusting one constant in the combined severity parameter (CSP) provided a rapid and accurate tool for trading off times, temperatures, and acid concentrations to reach the highest xylose yields from xylooligomers in hydrothermal pretreatment solutions. This adjusted CSP showed that an 8.4 °C temperature increase has the same impact as doubling the acid concentration or halving reaction time instead of the 10 °C change projected by the customary CSP and suggests that xylooligomers bonds are more easily broken than the hemicellulose from which they are derived.